2010
DOI: 10.1016/j.mri.2010.03.037
|View full text |Cite
|
Sign up to set email alerts
|

On the sensitivity of ASL MRI in detecting regional differences in cerebral blood flow

Abstract: Arterial-spin-labeling (ASL) MRI provides a non-invasive tool to measure cerebral blood flow (CBF) and is increasingly used as a surrogate for baseline neural activity. However, the power of ASL MRI in detecting CBF differences between patient and control subjects is hampered by inter-subject variations in global CBF, which are associated with non-neural factors and may contribute to the noise in the across-group comparison. Here, we investigated the sensitivity of this technique and proposed a normalization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 32 publications
5
83
0
Order By: Relevance
“…To minimize intersubject variations of CBF and to increase the sensitivity of this imaging technique, we used whole-brain normalization and voxel-based analysis of ASL MR imaging, as previously described in cognitive studies. 7 At the group level, we were able to display preoperative hypoperfusion in the MCA territory and a postoperative increase of CBF perfusion, therefore validating the surgical technique. At the individual level, FIG 5.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…To minimize intersubject variations of CBF and to increase the sensitivity of this imaging technique, we used whole-brain normalization and voxel-based analysis of ASL MR imaging, as previously described in cognitive studies. 7 At the group level, we were able to display preoperative hypoperfusion in the MCA territory and a postoperative increase of CBF perfusion, therefore validating the surgical technique. At the individual level, FIG 5.…”
Section: Discussionmentioning
confidence: 57%
“…Because children under-going an operation for MM need repeated quantification of their CBF before and after surgery, ASL MR imaging may be of particular interest, and statistical approaches, as described with statistical parametric analysis (SPM) of ASL MR imaging in cognitive series, may allow intraindividual and group analysis of CBF comparisons before and after the operation. 7 This could allow a noninvasive follow-up of patients having undergone an operation and help to prevent recurrent stroke in patients with persistent hypoperfusion.…”
mentioning
confidence: 99%
“…Despite some limitations, this study adds to the literature on statistical inference in functional neuroimaging and the results were in a range established in previous sample-size estimations (Aslan and Lu, 2010;Murphy et al, 2011;Desmond and Glover, 2002;Murphy and Garavan, 2004). Sample size requirements determined using FEAT were comparable to previous work on sample-size estimation where BOLD MRI acquisition was used (Desmond and Glover, 2002;Murphy and Garavan, 2004).…”
Section: Discussionmentioning
confidence: 55%
“…A BOLD-based fMRI study for an unpaired design scenario reported that 20 subjects per group could be sufficient for 80% power in reproducing truly activated voxels (Murphy and Garavan, 2004). A study based on ASL data has reported similar numbers of 20 subjects per group for a moderate 10% group perfusion difference at 80% power (Aslan and Lu, 2010), or between 20 to 40 subjects per group from an ROI analysis in Murphy et al (Murphy et al, 2011). The higher sample size requirement in Randomise as compared to previous sample size studies may be consequence of the stringent permutation approach applied to control for multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation